Clinical Significance of Volume Status in Body Composition and Physical Performance Measurements in Hemodialysis Patients - Kim, Jun Chul; Do, Jun Young; Kang, Seok Hui (Frontiers in Nutrition, 2022)
Introduction This study aimed to evaluate the association between volume status and body composition or physical performance measurements in hemodialysis patients. Methods A total of 84 patients were enrolled in this study. The participants were divided into tertiles based on the edema index (extracellular water/total body water): low, middle, and high tertiles. Serum albumin and serum high-sensitivity C-reactive protein levels were measured. The appendicular lean mass index (ALM/Ht2, kg/m2) was measured using dual-energy X-ray absorptiometry. The thigh muscle area index (TMA/Ht2, cm2/m2) was measured using CT. Extracellular and total body water and phase angles were obtained using bioimpedance analysis. The results of the subjective global assessment (SGA), hand-grip strength (HGS), gait speed (GS), short physical performance battery (SPPB), sit-to-stand for 30-second (STS30) test, timed up and go (TUG), sit-to-stand test performed five times (STS5), and 6-minute walk (6-MW) tests were also evaluated. Results On the univariate analysis, the SGA score and phase angle in the high tertile group were the lowest among the three groups. On multivariate analysis, TMA/Ht2 and phase angle in the high tertile were the lowest among the three groups. Inverse correlations were observed between edema index and TMA/Ht2, SGA score, phase angle, HGS, GS, SPPB, STS30, or 6-MW. Positive correlations were observed between the edema index and the STS5 or TUG test. The sensitivity and specificity for predicting low GS were 34.5 and 89.7%, respectively. The values for predicting low SPPB were 68.0 and 79.7%, respectively. Conclusion This study demonstrates that high volume status may be associated with decreased muscle mass and physical performance regardless of inflammatory or nutritional status.